The analytical unity of personality: basic behavioral repertoires or interactive styles? - William Montgomery Urday (Interacciones)
As alternative options to the traditional use of the traits, the proposals of unity of analysis of the personality offered by two behavioral approaches selected taking into account their pertinence and validity are mentioned: that of the "basic behavioral repertoires", and that of the "interactive styles", quantitatively evaluating them according to their respective degrees of conformity with guidelines of theoretical and practical utility (if they generate research, if they are refutable, if they organize the data, if they serve as a guide, if they have internal coherence and are simple). It is concluded that both proposals have a good livelihood, with a slight advantage (for its greater simplicity) for the basic behavioral repertoires.